Highgate Cemetery Heterotopia: A Creative Counterpublic Space. (November 2017) - Clements, Paul
Highgate Cemetery is nominally presented as a heterotopia, constructed, and theorized through the articulation of three "spaces." First, it is configured as a public space which organizes the individual and the social, where the management of death creates a relationship between external space and its internal conceptualization. This reveals, enables, and disturbs the sociocultural and political imagination which helps order and disrupt thinking. Second, it is conceived as a creative space where cemetery texts emplace and materialize memory that mirrors the cultural capital of those interred, part of an urban aesthetic which articulates the distinction of the metropolitan elite. Last, it is a celebritized counterpublic space that expresses dissent, testimony to those who have actively imagined a better world, which is epitomized by the Marx Memorial. Representation of the cemetery is ambiguous as it is recuperated and framed by the living with the three different "spaces" offering heterotopic alliances.